The macro and micro-structure of the celiac and cranial mesenteric ganglia in a long-lived rodent – paca (Cuniculus paca, linnaeus 1766) - Rabello, Victor Crestana [UNESP] (2021)
The celiac, cranial mesenteric and celiacomesenteric ganglia of the paca (Cuniculus paca) were found between the celiac and cranial mesenteric arteries. Two predominant patterns were found: isolated celiac and cranial mesenteric ganglion and the celiacomesenteric ganglion. At the microscopic level, the ganglia are constituted by an agglomeration of neurons surrounded by capsule of connective tissue. Most of these neurons had a single eccentric nucleus. Satellite cells and mast cells were found around the soma. The mast cells were also found ar ound blood vessels and in the capsule of the ganglia.